Poly(2‐ethyl‐2‐oxazoline) as a Gel Additive to Improve the Performance of Sulfur Cathodes in Lithium‐Sulfur Batteries. Issue 2 (27th January 2021) - Yang, Qi; Yu, Yu; Huang, Wenlong; Liu, Yuansheng; Liu, Xu; Liu, Huitian; Shan, Zhongqiang
Abstract: Dissolution and free diffusion of polysulfides in ether‐based electrolyte during cycling causes fast capacity decay and low columbic efficiency in lithium‐sulfur batteries. In this work, poly(2‐ethyl‐2‐oxazoline) (PEtOx), as an additive of sulfur cathodes, can gelatinate the electrolyte in the presence of polysulfide species, which can anchor the uncontrollable diffusion of polysulfides during the discharge process. Additionally, pore structures can form in the sulfur cathode after the dissolution of PEtOx into the electrolyte. As a result, the sulfur converted from polysulfides during subsequent charging processes will deposit more uniformly in the porous cathode. This "dissolution‐redeposition" mechanism effectively reduces the loss of active materials, providing beneficial guidance for practical Li−S batteries. Abstract : Dissolution and redeposition : Pore structures can form in the sulfur cathode after the dissolution of PEtOx into the electrolyte, which gelatinates the electrolyte in the presence of polysulfide species. As a result, the sulfur converted from polysulfides during subsequent charging processes will deposit more uniformly in the porous cathode. This "dissolution‐redeposition" mechanism effectively reduces the loss of active materials and improves the performance of sulfur cathodes, providing beneficial guidance for practical Li−S batteries.